Hanami Capsule Hotel / Wan Nur Husna Abdul Nasir - Abdul Nasir, Wan Nur Husna (2020)
Hanami Capsule Hotel services for customer, providing the service accommodation and service food that gives high satisfaction of human or customer. Customer Hanami Capsule Hotel majority come from a variety of ages and background, but the concept offer to customer like more focus on bagpack, solo, teammates, partner and small family because the customer will find or prefer a hotel with no big space, simple, temporary accommodation and so on. Location Hanami Capsule Hotel at Cameron Highland, business has see an explosion of growth over the month and year. Also, Cameron Highland is an famous place that many people go travel or overseeing espically time school holiday, public holiday and so on. Hanami Capsule Hotel marketing strategy is give the best quality for service what Hanami Capsule Hotel offer to customer. In addition, offer the afforable price because not everyone can afford to stay at an expensive price and the original purpose Hanami Capsule Hotel is to give excellent knowledge so we want everyone to feel and enjoy the service provide by hotel also satisfaction the target customer.